Promoting the general welfare : new perspectives on government performance - Gerber, Alan S.; Patashnik, Eric M. (Brookings Institution Press, 2006)
"Analyzes government's ability to "promote the general welfare" in the areas of health, transportation, housing, and education. Then examines two tools to improve policy design: information markets and laboratory experiments. Concludes by asking how Congress, the party system, and federalism affect government's ability to solve important social problems"--Provided by publisher